2020
DOI: 10.3390/cells9112379
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Properties of the Ccr4–Not Complex

Abstract: The mammalian Ccr4–Not complex, carbon catabolite repression 4 (Ccr4)-negative on TATA-less (Not), is a large, highly conserved, multifunctional assembly of proteins that acts at different cellular levels to regulate gene expression. In the nucleus, it is involved in the regulation of the cell cycle, chromatin modification, activation and inhibition of transcription initiation, control of transcription elongation, RNA export, nuclear RNA surveillance, and DNA damage repair. In the cytoplasm, the Ccr4–Not compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 416 publications
(643 reference statements)
0
36
0
Order By: Relevance
“…To further verify the involvement of Tex13a in the RNA metabolism, we analyzed the potential association of Tex13a with the CCR4–NOT complex, which serves as a key RNA machine participating in the initial step of RNA degradation. Among the several important components of the CCR4–NOT complex, Cnot1 was the largest and main structural component with five domains ( Chalabi Hagkarim and Grand, 2020 ). The five domains annotated by Pfam have been shown in Figure 2A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further verify the involvement of Tex13a in the RNA metabolism, we analyzed the potential association of Tex13a with the CCR4–NOT complex, which serves as a key RNA machine participating in the initial step of RNA degradation. Among the several important components of the CCR4–NOT complex, Cnot1 was the largest and main structural component with five domains ( Chalabi Hagkarim and Grand, 2020 ). The five domains annotated by Pfam have been shown in Figure 2A .…”
Section: Resultsmentioning
confidence: 99%
“…Among these pathways, the CCR4–NOT complex can effectively degrade poly(A) tails of mRNAs and initiate the early as well as the rate-limiting step of mRNA turnover ( Wahle and Winkler, 2013 ). The CCR4–NOT complex, as a core and non-specific scissor for poly(A) tail, normally requires the help of other special partners, such as 3′-UTR regulatory elements and a variety of trans- acting factors, to trigger targeted decay of specific mRNAs ( Mayya and Duchaine, 2019 ; Chalabi Hagkarim and Grand, 2020 ). Cnot1 is the largest subunit of the core CCR4–NOT complex and provides the backbone for other subunits to associate together ( Temme et al, 2014 ; Chalabi Hagkarim and Grand, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, METTL3-mediated m 6 A methylation of SPHK2 targets KLF2, thus promoting advanced GC (10). Human CCR4 and CAF1 deacetylase mediate the regulation of human GC cell proliferation and tumorigenicity via modulating the cell cycle process (11). Understanding the regulatory mechanism of GC will offer new insights into treating GC (12).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its association with nuclear RNA degradation factors in mitotic cells, Mmi1 also tightly associates with the evolutionarily conserved Ccr4-Not complex [ 37 , 56 , 57 , 58 , 59 ], the major mRNA deadenylase involved in cytoplasmic mRNA turnover [ 60 , 61 ]. Surprisingly, we previously found that efficient meiotic mRNA degradation does not require the deadenylation activity of the complex but instead depends on the integrity of the E3 ubiquitin ligase subunit Not4/Mot2 [ 59 ].…”
Section: The Lncrna Mamrna Scaffolds the Antagonistic Rna-binding Proteins Mmi1 And Mei2 To Exert Their Mutual Inhibitmentioning
confidence: 99%